Nordisk forskning och exempel på validering - Andersson, Per; Stenlund, Tova (Linköpings universitet, Avdelningen för studier av vuxenutbildning, folkbildning och högre utbildning (VUFo), 2012)
This report is about validation, or recognition/accreditation of prior learning, in the Nordic countries – Denmark, Finland, Iceland, Norway, and Sweden. The aim of the report is to analyse cases of validation practice in the Nordic countries in relation to a number of central concepts (see below), and to present a review of Nordic research on validation. The review of research shows that validation research has mainly been conducted in Sweden, with a few additional examples from the other Nordic countries. This research has applied varying theoretical perspectives to interpret different aspects of the validation process. Theories on learning, governing, communication, gender, organising, and validity, have been used to develop the understanding of validation. Considering the efforts made for developing validation in practice, further development could be expected also when it comes to research. This could contribute further to understanding and development of Nordic validation practice and conditions for lifelong learning. The cases from validation practice in the Nordic countries have been selected to cover both cases of validation targeting specific groups, and cases relating to flexibility in working life. The central concepts that have been the starting point in the analysis are inclusion, mobility, flexibility, empowerment, and employability. The result shows good examples of validation that empower and include specific target groups, such as immigrants, prisoners, unskilled, and persons with reading and writing problems, in working life. This is often implemented by improving their formal educational level, and thereby their employability. The cases further show that initiatives to improve mobility and flexibility are taken both in the private sector, e.g. banking, finance, and industry, and in the public sector, e.g. among paramedics and mail staff. However, there are also problems on a societal level, e.g. related to structural economic aspects, and on an individual level, e.g. resistance and suspicion ...